Biodegradable carbon dioxide-based polycarbonate as well as preparation method and application thereof

By introducing neopentyl glycol diglycidyl ether into carbon dioxide-based polycarbonate to form alternating copolymer PPCN, the problems of poor biodegradation effect and poor mechanical properties of existing materials are solved, and higher thermal stability and biodegradation performance are achieved.

CN119899364APending Publication Date: 2025-04-29XI'AN PETROLEUM UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510200512.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing carbon dioxide-based polycarbonate has poor biodegradation effect and poor mechanical properties of materials.

Method used

Neopentyl glycol diglycidyl ether is used as the third monomer to compete for insertion in the copolymerization reaction with carbon dioxide and propylene oxide to form a more stable alternating copolymer PPCN, which improves the thermal stability and biodegradation performance of the polymer.

Benefits of technology

It improves the thermal stability and biodegradability of carbon dioxide-based polycarbonate, enhances the mechanical properties and biocompatibility of the materials, and reduces the impact of traditional materials on the ecological environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899364A_ABST
    Figure CN119899364A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon dioxide-based polycarbonate, and discloses biodegradable carbon dioxide-based polycarbonate and a preparation method and application thereof.The preparation method comprises the steps that epoxypropane, neopentyl glycol diglycidyl ether and a catalyst are mixed, CO2 is introduced till the pressure is 2-4 MPa, a reaction is conducted for 8-14 h at the temperature of 20-50 DEG C, the mixture obtained after the reaction is purified, and the biodegradable carbon dioxide-based polycarbonate is obtained. The carbon dioxide-based polycarbonate is obtained; wherein the catalyst is one of a cobalt catalyst, a double metal cyanide catalyst, a metalloporphyrin catalyst or a zinc glutarate catalyst. According to the invention, neopentyl glycol diglycidyl ether is used as a third monomer and is introduced into a copolymerization reaction during polymerization, carbon dioxide and neopentyl glycol diglycidyl ether are competitively inserted to rearrange the structure of PPC, a more stable alternating copolymer PPCN is formed, and breakage and separation of a polymer chain are effectively prevented, so that the thermal stability is improved; the carbon dioxide-based polycarbonate with the enzymatic degradation characteristic has narrow molecular weight distribution and high yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon dioxide-based polycarbonate, and in particular relates to a biodegradable carbon dioxide-based polycarbonate and a preparation method and application thereof. Background Art

[0002] Since the birth of the petroleum industry, the plastics industry has become an important petrochemical branch and has achieved extensive development. Plastics are one of the world's three major organic synthetic materials. Their applications in various social fields are becoming increasingly widespread, and the global plastic consumption problem is prominent. Traditional plastic products are mainly made of petroleum-based polymers such as polyethylene (PE), polyvinyl chloride (PVC), polypropylene (PP) and polyamide (PA), which are favored for their high molecular weight, durability, aging resistance and corrosion resistance. However, their environmental stability makes it difficult for them to degrade naturally, thus causing serious damage to the environment, which is often referred to as "white pollution". Current research shows that more than 60% of waste plastics are either landfilled or discarded, which has prompted the global scientific community to begin seeking biodegradable alternative solutions. In addition, the booming petroleum industry has also caused serious carbon emissions, exacerbating the greenhouse effect. The difficulties faced by the plastics industry and the continuous accumulation of carbon dioxide in the atmosphere prompted Japanese scientist Professor Inoue to explore the addition of carbon dioxide activation in copolymerization reactions in 1969, marking the advent of carbon dioxide-based polycarbonate materials. After more than five decades of development, these materials have become one of the top five engineering plastics for their excellent flexibility, effective water vapor barrier, biodegradability, and biocompatibility. Among these engineering plastics, polyamide (PA), polyoxymethylene (POM), and polyphenylene oxide (PPO) release toxic substances when degraded; while polyester materials (PET / PBT) degrade slowly and release benzene rings. Therefore, with the tightening of environmental regulations and the growing demand for sustainable materials, polycarbonate materials, especially those synthesized from CO2, are becoming more and more popular. These materials have made breakthrough progress in CO2 activation and ring-opening polymerization catalysts and are increasingly being seen as viable environmentally friendly alternatives. Currently, polyesters such as polylactic acid (PLA) and polybutylene succinate (PBS) dominate the biodegradable plastics market. However, the booming polycarbonate industry, especially CO2-based variants, shows strong growth momentum and potential due to their effective degradation characteristics and the maturity of CO2 activation technology. The current method to improve the degradability of CO2-based polycarbonate mainly utilizes physical mixing modification. The main synthetic polymers blended with PPC include PBS, polyhydroxybutyrate (PHB), polymethyl methacrylate (PMMA), polycaprolactone (PCL) and polyhydroxyalkanoate (PHA), and the copolymers have better degradability than pure PPC materials. In addition, mixing PPC with natural polymers such as cellulose and its derivatives, starch, chitosan, eggshell powder, waste tea powder and waste wood powder usually produces beneficial modification effects. Due to the inherent biodegradability of natural polymers, their composites with PPC can remain completely degraded, thereby reducing environmental pressure.

[0003] In the process of synthesizing degradable polycarbonate by copolymerization of carbon dioxide and propylene oxide, the introduction of common third monomer is only to improve its thermal and mechanical properties. In order to improve the mechanical properties of the material, the modified monomers selected by the traditional ternary modification all have benzene rings, and the mechanical properties of the material are enhanced by the rigidity of the benzene rings. However, the introduction of the benzene rings will inevitably cause the toxicity and insecurity of the degradation products. The neopentyl glycol diglycidyl ether adopted in the present invention is a long-chain cross-linking agent without benzene rings. Although it does not have a rigid structure itself, it will form a cross-linked structure after irregular alternating copolymerization with carbon dioxide, which enhances the mechanical and thermal properties of the polymer while maintaining the environmental protection characteristics of the carbon dioxide-based polycarbonate material. At the same time, the chemical structure of glycidyl ether is similar to propylene oxide, which can provide more recognition and binding sites for lipase, and promote the biodegradation characteristics of the material. Summary of the invention

[0004] The invention provides a biodegradable carbon dioxide-based polycarbonate and a preparation method and application thereof, which solve the problems of poor biodegradation effect and poor mechanical properties of materials in the prior art.

[0005] The first aspect of the present invention provides a method for preparing a biodegradable carbon dioxide-based polycarbonate, the preparation method comprising:

[0006] After mixing propylene oxide, neopentyl glycol diglycidyl ether and the catalyst, CO 2 until the pressure reaches 2-4 MPa, react at 20-50° C. for 8-14 hours, and purify the reaction mixture to obtain carbon dioxide-based polycarbonate;

[0007] Wherein, the catalyst is one of a cobalt catalyst, a double metal cyanide catalyst, a metal porphyrin catalyst or a zinc glutarate catalyst.

[0008] Preferably, the molar ratio of propylene oxide, catalyst and neopentyl glycol diglycidyl ether is 10000:(1-3):1000-5000.

[0009] Preferably, the cobalt catalyst is Salen[Co(III)TFA] 2 .

[0010] Preferably, the purification method comprises:

[0011] The mixture after the reaction is first added into chloroform containing 5% hydrochloric acid solution to terminate the reaction, and then poured into methanol for precipitation. The obtained precipitate is carbon dioxide-based polycarbonate.

[0012] Preferably, the catalyst is vacuum dried at 70° C. for 7-9 hours before the reaction.

[0013] The second purpose of the present invention is to protect the carbon dioxide-based polycarbonate prepared by the method for preparing the biodegradable carbon dioxide-based polycarbonate.

[0014] Preferably, one of its chemical structural formulas is:

[0015]

[0016] The third object of the present invention is to protect the use of the biodegradable carbon dioxide-based polycarbonate in the preparation of degradable packaging materials or degradable barrier materials.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The preparation method of carbon dioxide-based polycarbonate provided by the present invention comprises the following steps: using neopentyl glycol diglycidyl ether as the third monomer, which is introduced into the carbon dioxide-based polycarbonate during polymerization; during the polymerization reaction, carbon dioxide and neopentyl glycol diglycidyl ether are competitively inserted to rearrange the structure of PPC, thereby forming a more stable alternating copolymer PPCN, which effectively prevents the breakage and separation of the polymer chain, thereby improving the thermal stability, and making the carbon dioxide-based polycarbonate with enzyme degradation characteristics have a narrow molecular weight distribution and high yield; making the prepared carbon dioxide-based polycarbonate contain more hydroxyl groups and ester groups, so as to improve its degradation performance, enhance biocompatibility, and reduce toxicity; and reducing the brittleness of the PPC material itself through the formation of a cross-linked structure, thereby achieving a toughening effect; using a ring-opening catalyst Salen[Co(III)TFA] 2 , introducing additional hydroxyl groups and ester groups into the polymer. This structural change helps to build stable hydrogen bonds with water molecules, significantly improving hydrophilicity. In addition, the introduction of more ester bonds can provide more enzyme cleavage sites, greatly improving the efficiency of enzyme-mediated degradation.

[0019] 2. The carbon dioxide-based polycarbonate provided by the present invention has better bioaffinity, degradation characteristics, mechanical strength, and flexibility; and is completely biodegradable, which consumes carbon dioxide greenhouse gas and alleviates the greenhouse effect while greatly reducing the impact of traditional materials on the ecological environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 The synthetic flow chart of PPCN prepared in the examples of this application;

[0022] Figure 2 This is a comparison chart of infrared spectra of PPCN, PPC and N prepared in the examples of the present application;

[0023] Figure 3 A comparison chart of the mechanical properties of PPCN1, PPCN2, PPCN3, PPCN4, PPCN5, PPCN6, and PPC prepared in the examples of this application;

[0024] Figure 4 This is a graph showing the mass change rate of PPCN prepared in the present application example under the action of different enzymes;

[0025] Figure 5 This is the apparent morphology of the PPCN prepared in the examples of this application after being degraded by different enzymes;

[0026] Figure 6 This is a GC-MS analysis chart of the degradation product of PPCN prepared in the examples of the present application. DETAILED DESCRIPTION

[0027] The technical solutions in the present invention will be described clearly and completely below in conjunction with the specific implementation of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0029] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".

[0030] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0031] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.

[0032] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values ​​in the stated range are also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0033] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those generally understood by those skilled in the art to which the present application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0034] It should be noted that the catalyst used in the present invention is one of a cobalt catalyst, a double metal cyanide catalyst, a metal porphyrin catalyst or a zinc glutarate catalyst. Wherein, these catalysts all have a higher catalytic activity that causes a ring-opening copolymerization reaction. Specifically, these types of catalysts can all activate carbon dioxide by forming a chemical bond (such as a coordination bond) with a carbon dioxide molecule. Carbon dioxide is a relatively stable molecule, and its carbon-oxygen double bond has a higher bond energy. These catalysts can utilize their own active center to coordinate with the carbon atom or oxygen atom of carbon dioxide, so that the molecular structure of carbon dioxide is changed, and the intensity of the carbon-oxygen double bond is weakened. For example, in the copolymerization reaction of catalytic carbon dioxide and epoxide, the catalyst first activates carbon dioxide so that it can react more easily with the epoxide molecule, open the epoxy ring group of epoxide, and then form polycarbonate.

[0035] It should be noted that the reagents used in the experiment, propylene oxide (PO), neopentyl glycidyl ether (NGDE), anhydrous ethanol and dichloromethane (DCM) were all analytically pure and purchased from Shanghai MacLean Biochemical Co., Ltd. and were used directly.

[0036] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0037] Example 1

[0038] A method for preparing biodegradable carbon dioxide-based polycarbonate (PPCN1), comprising:

[0039] (1) 0.01 mol Salen[Co(III)TFA] 2 Place in an autoclave reactor equipped with a magnetic stirrer and dry under vacuum at 70 °C for 7 h to complete drying;

[0040] (2) After drying, the autoclave reactor was purged with nitrogen, 1000 mol of propylene oxide and 10 mol of neopentyl glycol diglycidyl ether were injected into the autoclave reactor, and then CO was charged into the autoclave reactor. 2 until the pressure reaches 3MPa; the molar ratio of propylene oxide to neopentyl glycol diglycidyl ether is 100:1. Then, the terpolymerization reaction is carried out at 35°C for 10 hours, the reaction is stopped, cooled to room temperature, the pressure is released, and the product is collected. The product is a viscous liquid;

[0041] (3) The viscous liquid obtained in step (2) is first added to chloroform containing 5% hydrochloric acid solution to terminate the reaction, and then poured into methanol for precipitation twice. The resulting precipitate is carbon dioxide-based polycarbonate, abbreviated as PPCN1. The specific synthesis formula is shown in Figure 1 .

[0042] according to Figure 2 As shown in the figure, the infrared spectra of the aliphatic polycarbonate PPC and neopentyl glycol diglycidyl ether NGDE prepared by the alternating copolymerization of the carbon dioxide-based polycarbonate PPCN prepared in this embodiment with carbon dioxide and propylene oxide are compared, and it can be clearly seen that the infrared spectra of 908 cm -1 The characteristic absorption peak of the epoxy group in the monomer NGDE is shown in the 908cm-1 spectrum of the PPCN spectrum. -1 The characteristic absorption peak of the epoxy group at 1098cm-1 basically disappeared, indicating that the epoxy group participated in the chemical reaction and formed other new groups. -1 This is the stretching vibration peak of the ether bond in the monomer NGDE, which still appears in the spectrum of the ternary polymer PPCN. -1 The peak at 1740 cm-1 in the PPCN spectrum can be attributed to the stretching vibration peak of CO in the ester bond of polycarbonate PPCN. In addition, compared with the spectrum of the third monomer NGDE, the peak at 1740 cm-1 in the PPCN spectrum -1 A new strong absorption peak appeared at , which is the stretching vibration peak of the C=O group in polycarbonate. It can be clearly seen that the ternary polymer PPCN1 was successfully synthesized.

[0043] Example 2

[0044] A method for preparing biodegradable carbon dioxide-based polycarbonate (PPCN2), comprising:

[0045] (1) Add 0.04mol Salen[Co(III)TFA]2 Place in an autoclave reactor equipped with a magnetic stirrer and dry under vacuum at 70 °C for 8 h to complete drying;

[0046] (2) After drying, the autoclave reactor was purged with nitrogen, 1000 mol of propylene oxide and 0.04 mol of neopentyl glycol diglycidyl ether were injected into the autoclave reactor, and then CO was charged into the autoclave reactor. 2 until the pressure reaches 2MPa; the molar ratio of propylene oxide to neopentyl glycol diglycidyl ether is 100:1. Then, the terpolymerization reaction is carried out at 40°C for 12h, the reaction is stopped, cooled to room temperature, the pressure is released, and the product is collected. The product is a viscous liquid;

[0047] (3) The viscous liquid obtained in step (2) is first added to chloroform containing 5% hydrochloric acid solution to terminate the reaction, and then poured into methanol for precipitation three times. The resulting precipitate is carbon dioxide-based polycarbonate, abbreviated as PPCN2.

[0048] Example 3

[0049] A method for preparing biodegradable carbon dioxide-based polycarbonate (PPCN3), comprising:

[0050] (1) 0.09 mol Salen[Co(III)TFA] 2 Place in an autoclave reactor equipped with a magnetic stirrer and dry under vacuum at 70 °C for 9 h to complete drying;

[0051] (2) After drying, the autoclave reactor was purged with nitrogen, 1000 mol of propylene oxide and 30 mol of neopentyl glycol diglycidyl ether were injected into the autoclave reactor, and then CO was charged into the autoclave reactor. 2 until the pressure reaches 2MPa; the molar ratio of propylene oxide to neopentyl glycol diglycidyl ether is 100:1. Then, the terpolymerization reaction is carried out at 40°C for 14h, the reaction is stopped, cooled to room temperature, the pressure is released, and the product is collected. The product is a viscous liquid;

[0052] (3) The viscous liquid obtained in step (2) is first added to chloroform containing 5% hydrochloric acid solution to terminate the reaction, and then poured into methanol for precipitation twice. The resulting precipitate is carbon dioxide-based polycarbonate, abbreviated as PPCN3.

[0053] Example 4

[0054] The composition ratio, preparation operation and process parameters of PPCN4 provided in this embodiment are basically the same as those in Example 1, except that the molar ratio of neopentyl glycol diglycidyl ether to propylene oxide used as the raw material in this embodiment is 4%, and PPCN4 is prepared.

[0055] Example 5

[0056] The composition ratio, preparation operation and process parameters of PPCN5 provided in this embodiment are basically the same as those in Example 1, except that the molar ratio of neopentyl glycol diglycidyl ether to propylene oxide used as the raw material in this embodiment is 5%, and PPCN5 is prepared.

[0057] The process parameters of Examples 1-5 are summarized as shown in Table 1:

[0058] Table 1 List of process parameters for Examples 1-5

[0059]

[0060] At the same time, in order to verify the comprehensive performance of the carbon dioxide-based polycarbonate prepared in the above examples, the present invention provides the following comparative examples for detailed description.

[0061] Comparative Example 1

[0062] In this comparative example, the polypropylene carbonate (PPC) purchased from Jiangsu Zhongke Jintai Technology Co., Ltd. in Example 1 is used as comparative example 1.

[0063] Comparative Example 2

[0064] In this comparative example, neopentyl glycol diglycidyl ether (NGDE) purchased from Shanghai MacLean Biochemical Co., Ltd. in Example 1 is used as comparative example 2.

[0065] In order to verify the comprehensive performance of the carbon dioxide-based polycarbonate prepared in the embodiment of the present invention, corresponding performance tests were performed on it:

[0066] 1. Gel Permeation Chromatography Analysis

[0067] The carbon dioxide-based polycarbonate prepared in the example was subjected to gel permeation chromatography analysis and testing, and the results are shown in Table 2:

[0068] Table 2 Gel permeation chromatography analysis results of PPCN prepared in different groups

[0069]

[0070] According to Table 2, compared with the traditional binary polymer and ternary end-capped polymer, the PPCN prepared by the present invention has a higher molecular weight and a lower dispersibility index, a more balanced molecular weight distribution, and a more uniform material. When the molar ratio of neopentyl glycol diglycidyl ether to propylene oxide is 4%, its yield and relative molecular mass are higher.

[0071] 2. Thermal performance test

[0072] (1) Glass transition temperature: The glass transition temperature was measured by differential scanning calorimetry (DSC) of Mettler-Toledo Corporation on a Q100TA analyzer. The sample was heated from 25°C to 200°C at a heating rate of 10°C / min in a nitrogen atmosphere.

[0073] (2) Maximum thermal decomposition temperature: The test was conducted using a thermogravimetric analyzer (TGA / DSC-1) from Mettler-Toledo, USA. The sample was heated from 25°C to 500°C at a heating rate of 10°C / min in 10 ml / min nitrogen. The test results are shown in Table 3:

[0074] Table 3 Thermal performance test results of PPCN prepared in different groups

[0075] Group <![CDATA[T g (℃)]]> <![CDATA[T -5% (℃)]]> <![CDATA[T max (℃) <!-- 6 -->]]> PPC 31 150 260 PPCN1 37 210 309 PPCN2 38 212 312 PPCN3 39 218 320 PPCN4 40 225 325 PPCN5 38 215 318

[0076] According to Table 3, the thermal performance of the PPCN prepared in the example is evaluated, and when the molar ratio of neopentyl glycol diglycidyl ether to propylene oxide is 4%, the glass transition temperature and the maximum thermal decomposition temperature are optimal.

[0077] 3. Mechanical properties test:

[0078] The samples were molded into dumbbell shapes (25 mm × 4 mm × 1 mm) according to ASTM E104 standard, and their mechanical properties were evaluated using an Instron 5969 electronic universal material testing machine at a tensile speed of 50 mm / min at room temperature. Each group of samples was repeated three times and the results were averaged. The test results are shown in Table 4 and Figure 3 As shown:

[0079] Table 4 Mechanical properties test results of PPCN prepared in different groups

[0080]

[0081]

[0082] According to Table 4 and Figure 3It can be seen that the tensile strength and Young's modulus of the binary polymer PPC are low, 15.2MPa and 389MPa, respectively, and the elongation at break is high. After adding the third monomer NGDE, the tensile strength and Young's modulus of PPCN are higher than those of the binary polymer PPC, while the elongation at break decreases. When the addition amount of NGDE is 4%, the tensile strength and Young's modulus of PPCNs are 22.5MPa and 1012MPa, respectively. The introduction of the third monomer NGDE increases the rigidity of the polycarbonate molecular chain, thereby hindering the movement of the molecular chain. In addition, the introduction of NGDE increases the molecular weight of the polymer and helps to improve the interaction between molecules. Both factors lead to an increase in the Young's modulus and tensile strength of the copolymer. In addition, compared with pure PPC, the elongation at break of the terpolymer PPCN decreases. When the molar ratio of NGDE to propylene oxide is 4%, the elongation at break of PPCN decreases from 312% to 166%.

[0083] 4. Degradation performance test:

[0084] (1) The present invention uses the carbon dioxide-based polycarbonate (PPCN4) prepared in Example 4 as an example to test the degradation characteristics:

[0085] The carbon dioxide-based polycarbonate (PPCN4) prepared in Example 4 was degraded with different enzymatic hydrolysates. A PPCN film was prepared in a culture dish by solution casting. PPCN and PPC were dried in a vacuum drying oven for 36 hours. Weigh and pour into chloroform respectively, stir evenly with a magnetic stirrer for 4-5 hours, prepare an 8wt% solution, and finally pour the solution into a culture dish and vacuum dry for 24 hours to obtain a complete and independent film. Cut the film into 5mm×5mm×1mm sizes, clean the cut edges of the PPC film with deionized water, and wipe with a rag to remove particles generated during the cutting process. Then air-dry the small PPC film, weigh and record.

[0086] Take 10 PPCN membranes, place them in 10 brown light-proof culture bottles, add 10 ml PBS solution, mark them as PPCN-Ⅰ-1, PPCN-Ⅰ-2, PPCN-Ⅰ-3, PPCN-Ⅰ-4, PPCN-Ⅰ-5, PPCN-Ⅰ-6, PPCN-Ⅰ-7, PPCN-Ⅰ-8, PPCN-Ⅰ-9, PPCN-Ⅰ-10, and record them as group Ⅰ; repeat the above operation, use the prepared mycobacterium lipase solution (group ⅠⅠ), septicagen solution (group ⅠⅠⅠ), malate dehydrogenase solution (group ⅠⅤ), porcine pancreatic lipase solution (group Ⅴ) instead of PBS solution, use Aspergillus niger lipase solution (group ⅤⅠ), and mark them well; repeat the operation of group Ⅰ, use PPC instead of PPCN, and record them as group ⅤⅠⅠ. All culture bottles are sealed and placed in a bacterial incubator. Take out one culture bottle from each group every week to characterize the degradation samples and degradation solutions.

[0087] according to Figure 4 As shown, it is a comparison diagram of the degradation mass loss of the carbon dioxide-based polycarbonate PPCN4 prepared in the embodiment in different enzymatic solutions, wherein the degradation environment of PPCN-Ⅰ is PBS solution (control), the degradation environment of PPCN-Ⅱ is rice root lipase solution, the degradation environment of PPCN-Ⅲ is sepsis lysozyme solution, the degradation environment of PPCN-Ⅳ is malate dehydrogenase solution, the degradation environment of PPCN-Ⅴ is porcine pancreatic lipase solution, the degradation environment of PPCN-Ⅵ is Aspergillus niger lipase solution, and the degradation environment of PPC-Ⅶ is PBS solution (control). Obviously, the degradation rate of the experimental group using lipase for degradation is generally higher than that of other groups, which indicates that there are binding sites for specific recognition of lipase in PPCN, which improves the enzymatic efficiency. In addition, the degradation rate of the group using PPCN as the substrate during the hydrolysis of PBS solution is always higher than that of the group using PPC as the substrate, indicating that the introduction of neopentyl glycol diglycidyl ether improves the degradation performance of PPC.

[0088] according to Figure 5 As shown, Figure 4 The instrument used for the microscopic morphology test of the materials in the experiment was a Zeiss DSM962 scanning electron microscope (SEM, Zeiss, Germany). After the sample was dried, gold was sputtered on the test surface at a voltage of 5 kV for imaging. 2The surface of the polycarbonate sample was smooth and flat before degradation. As the degradation time increased, wrinkles, holes, and fractures of varying degrees gradually appeared. As far as the entire degradation process is concerned, the degradation reaction induced by Rhizopus oryzae lipase mainly occurs on the polymer surface. When it was degraded in the enzymatic solution for 3W (21d), it can be seen from the scanning electron microscope that a large number of dot-like protrusions were generated on the surface of the polycarbonate, and there were some cracks on the protrusion surface; when it was degraded to 7W (49d), a large number of cracks appeared on the surface of the enzyme-eroded film under the action of enzymatic hydrolysis, and the surface of the film became increasingly rough; at 10W (70d), large-area cracks appeared in the experimental group degraded by lipase, proving that the "zipper degradation" effect had already occurred at this time.

[0089] (2) GC-MS analysis of degradation products: Although the reaction raw materials have shown non-toxic properties, characterizing the composition of the products is also crucial to clarify the environmentally friendly properties of a material. After 10 weeks of degradation, the degradation products of the degradation solution of the optimal degradation group were analyzed by GC-MS, such as Figure 6 shown.

[0090] according to Figure 6 It can be seen that the main degradation products of PPCN solution are propylene carbonate (elution time is 5.637 minutes) and dioctyl adipate (elution time is 32.950 minutes), both of which have high contents. In addition, ethylene glycol was detected at 3.703 minutes, dodecanol was detected at 15.863 minutes, and a small amount of other acids and alcohols. Therefore, the degradation products of PPCN materials are mainly composed of alcohols and esters, which are substances that can be recycled and converted by nature for the environment. Therefore, PPCN has environmentally friendly characteristics.

[0091] Therefore, the preparation method of carbon dioxide-based polycarbonate provided by the present invention uses neopentyl glycol diglycidyl ether as the third monomer, which is introduced into the carbon dioxide-based polycarbonate during polymerization. In the polymerization reaction, carbon dioxide and neopentyl glycol diglycidyl ether compete for insertion to rearrange the structure of PPC, forming a more stable alternating copolymer PPCN, effectively preventing the breakage and separation of the polymer chain, thereby improving thermal stability, so that the carbon dioxide-based polycarbonate with enzyme degradation characteristics has a narrow molecular weight distribution and high yield. In addition, the introduction of more ester bonds can provide more enzyme cleavage sites, thereby improving the efficiency of enzyme-mediated degradation.

[0092] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0093] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a biodegradable carbon dioxide-based polycarbonate, characterized in that: The preparation method comprises: After mixing propylene oxide, neopentyl glycol diglycidyl ether and a catalyst, CO2 is charged until the pressure reaches 2-4 MPa, and the mixture is reacted at 20-50°C for 8-14 hours, and the mixture after the reaction is purified to obtain a carbon dioxide-based polycarbonate; Wherein, the catalyst is one of a cobalt catalyst, a double metal cyanide catalyst, a metal porphyrin catalyst or a zinc glutarate catalyst.

2. The method for preparing biodegradable carbon dioxide-based polycarbonate according to claim 1, characterized in that: The molar ratio of propylene oxide, catalyst and neopentyl glycol diglycidyl ether is 10000:(1-3):1000-5000.

3. The method for preparing the biodegradable carbon dioxide-based polycarbonate according to claim 1, characterized in that: The cobalt catalyst is Salen[Co(III)TFA]2.

4. The method for preparing the biodegradable carbon dioxide-based polycarbonate according to claim 1, characterized in that: The purification method comprises: The mixture after the reaction is first added into chloroform containing 5% hydrochloric acid solution to terminate the reaction, and then poured into methanol for precipitation. The obtained precipitate is carbon dioxide-based polycarbonate.

5. The method for preparing biodegradable carbon dioxide-based polycarbonate according to claim 1, characterized in that: The catalyst was vacuum dried at 70° C. for 7-9 h before the reaction.

6. A carbon dioxide-based polycarbonate prepared by the method for preparing the biodegradable carbon dioxide-based polycarbonate according to any one of claims 1 to 5.

7. The biodegradable carbon dioxide-based polycarbonate according to claim 6, characterized in that: One of its chemical structural formula is:

8. Use of the biodegradable carbon dioxide-based polycarbonate according to any one of claims 6 to 7 in the preparation of degradable packaging materials or degradable barrier materials.

Citation Information

Patent Citations

  • Functional polycarbonate and preparation method thereof

    CN107446122A

  • Schiff base cobalt compound as well as preparation method thereof and preparation method of polycarbonate

    CN109054011A

  • Branched polyether carbonate polyols and method for their preparation

    EP2851384A1

  • Polycarbonate-based vitrimer materials and corresponding methods

    WO2024151868A2